Management of paediatric ankylosis - Neelam Noel Andrade; Prathmesh Kapoor; Paul Mathai; Varsha Gupta; V.K. Lakshmi; Shelly Sharma (Journal of Oral Biology and Craniofacial Research)
Temporomandibular joint ankylosis (TMJa) is one of the most crippling craniomaxillofacial pathological conditions characterized by replacement of normal architecture of temporomandibular joint (TMJ) with fibrous or bony tissue. The incidence of TMJa is most common in the paediatric population [first and second decades of life] and is commonly associated with maxillofacial trauma. Comprehensive management entails a thorough evaluation of the associated anatomy of the ankylotic mass and other pertinent details like the presence or absence of obstructive sleep apnoea. Categorizing patients based on these variables helps in selecting an appropriate surgical intervention. Various resective and reconstructive surgical techniques are discussed; along with their merits and demerits. Long-term physiotherapy, long-term clinical follow-up and appropriate family counselling are the essential pillars for success. In this review, the authors present an algorithmic approach to evaluation and management of paediatric TMJa. Appropriate recommendations are made based on evidence to select optimum surgical intervention.